(untitled) (Journal of Informatics Education and Research, 2024)
Agriculture is the source of livelihood of the majority of its population and being one of the most disaster prone countries, crop insurance occupies an important place in India. The plight of farmers in India is exacerbated by systemic neglect, pushing them to the margins of society. Crop failures resulting from natural disasters and adverse weather conditions add to their hardships, often leading to extreme despondency and tragically, suicides. Present study carried out to understand the effectiveness of PMFBY among farmers. A sample of 115 Farmers was considered to collect opinions through a structured questionnaire in Ramnagara and Tumkuru districts in Karnataka. The factors under the study were Awareness, Financial security, income stability, Loan repayment towards the future acceptance of effectiveness of the PMFBY among farmers.